Fatigue analysis of fibre-metal laminates for wind turbine applications - Sekar,Vinothini (Nanyang Technological University, 2020)
The offshore wind turbines are exposed to temperature, moisture and wind loads. The wind turbine blades should withstand all these factors. The fibre-metal laminates are suited for the wind turbine blade material. The fibre-metal laminates are used in the outer-shell and shear beams of the turbine blades. Glass fibre aluminium reinforced epoxy (GLARE) is a fibre-metal laminate which has specific advantages of aluminium and glass fibre/ epoxy. There are also different grades of GLARE that suits the different loading condition. For this project, the GLARE specimens of grade 2, 3 and 4 were fabricated. They were sub graded as type A and type B according to the orientation of glass fibre-epoxy layers. Six specimens were hygrothermal conditioned in an Environmental chamber. Six specimens were immersed in saltwater bath to simulate the seawater conditions. The tensile test, three-point bending test and fatigue test were conducted. The GLARE 2 showed the best tensile and bending properties. They are also easy to fabricate and less expensive, ranging from 2-10%, when compared to other grade GLARE material and aluminium 2024. The hygrothermal conditioning has adverse effect on the strength of the material. They degrade the mechanical properties of the GLARE material. The fatigue life of wet specimens was decreased significantly, about 14%, when compared to the dry specimens. The moisture absorption leads to early failure of the specimens.